Studi Tingkat Vandalisme Terhadap Softscape Oleh Pengguna Taman Di Lapangan I Gusti Ngurah Made Agung Denpasar - Novianty, Angela Sabrina; Semarajaya, Cokorda Gede Alit; Mayun, Ida Ayu (Jurnal Arsitektur Lansekap; Vol.7, No.2, Oktober 2021, 2021)
Study of vandalism level on softscape by park users at I Gusti Ngurah Made Agung Denpasar. This research was motivated by the existence of vandalism activities in I Gusti Ngurah Made Agung Park Denpasar as the result of human interactions between park user with their environment around this location as a public space. This study aims to identify level of vandalism and user perceptions of vandalism on softscape. The methods used in this research are survey method with collecting data techniques, observation, questionnaire distribution, and literature study. The result of this research showed that there are four variables that caused by vandalism on softscape in this area, such as scratching trees, nailing trees, littering around the plants and picking plants carelessly. The number of vandalism cases on softscape in this area reached about 13 cases that occurred with percentage 0.4% and western area or part of the field that is on Jalan Udayana is the area that received vandalism the most. Respondents in this study were visitors aged 12- 21 years old, which is the age of vandal on the park. The respondent’s perception of vandalism assumed that plants that are close or easy to reach by user and plants that have certain beauty or uniqueness are more vulnerable to be objects of vandalism. The low level of vandalism at I Gusti Ngurah Made Agung is still able to give users a sense of fun.